الإصلاحات التنظيمية للبلدية لمواكبة الإدارة الالكترونية (El-Wahat Journal for Research and Studies, 2021)
The Aim Of Introducing Information And Communication Technology In Municipal Work Is To Improve The Quality Of Administrative Services Entrusted To It. However, Municipal Reform To The Electronic System Is More Than Just A Restoration Of This Traditional Administrative Body. Rather, It Requires Adapting It To New Developments And Making It Capable Of Coping With Change. This Reform Includes Three Basic Points: Re-Engineering The Administrative Procedures So As To Change The Form Of Procedures Used To Suit The Principles Of Electronic Administration, The Development Of Serious Administrations Of Or Cancel Or Merge The Interests And Offices Of The List By Re-Engineering The Organizational Structure, Re-Engineering Powers. Keywords:  Municipality, Administrative Organization, Electronic Administration, Chairman Of Municipal People's Assembly, Secretary-General,